Whole genome sequencing of clinical isolates of Giardia lamblia. (February 2015) - Hanevik, K.; Bakken, R.; Brattbakk, H.R.; Saghaug, C.S.; Langeland, N.
Abstract: Clinical isolates from protozoan parasites such as Giardia lamblia are at present practically impossible to culture. By using simple cyst purification methods, we show that Giardia whole genome sequencing of clinical stool samples is possible. Immunomagnetic separation after sucrose gradient flotation gave superior results compared to sucrose gradient flotation alone. The method enables detailed analysis of a wide range of genes of interest for genotyping, virulence and drug resistance.